The talent project and the validation of standards for the identification of student-athlete talent - Vicari, D. S. S.; Bianco, A.; Albanese, M.; Capranica, L.; Doupona, M.; Koutavelis, E.; Alexandrou, G.; Tsivitanidou, O.; Gutovic, T.; Zelic, I.; Cular, D.; Mujkic, D.; et al. (Frontiers in Sports and Active Living, 2025)
Introduction: The aim of the TALENT project is to promote equality in education, prevent exclusion, support dual careers (sport and school), create new role models for the benefit of young talents and prepare them for lifelong learning and professional sport from an early age. It is promoted by a European consortium of 7 partner institutions and runs from December 2022 to May 2025. It consists of five work packages. In the first work phase, developing the WP2 (from December 2022 to October 2023), under the coordination of UNIPA, NIS University, KMOP and EAS standards for talent recognition were identified and validated.